2004
DOI: 10.1081/copd-120030829
|View full text |Cite
|
Sign up to set email alerts
|

Development of Self‐Administered Versions of Modified Baseline and Transition Dyspnea Indexes in COPD

Abstract: In this study we developed self-administered versions of modified baseline and transition dyspnea indexes and compared the scores obtained by this method with the mean value obtained by two trained interviewers. Twenty-five patients (14 males/11 females) with chronic obstructive disease who had a chief complaint of "breathlessness" were tested. Age was 66+/-11 years; forced expiratory volume in one second was 48+/-23% predicted. The baseline total scores were 5.0+/-1.8 for the interviewers and 5.4+/-2.0 for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
64
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 71 publications
(69 citation statements)
references
References 17 publications
4
64
0
1
Order By: Relevance
“…For example, disease severity in COPD patients based on spirometric classification is related to health status, utilization of health-care resources, development of exacerbations, and mortality. 3,26,27 Although cross-sectional studies 8,16,28,29 show modest correlations between measures of lung function and dyspnea ratings, previous investigators 27, 30 -32 have not shown significant differences in MRC dyspnea scores with different stages of COPD. Our results are the first to demonstrate that patient-reported dyspnea ratings on three different instruments are significantly related to the stage of disease severity based on percent predicted FEV 1 in patients with COPD.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations
“…For example, disease severity in COPD patients based on spirometric classification is related to health status, utilization of health-care resources, development of exacerbations, and mortality. 3,26,27 Although cross-sectional studies 8,16,28,29 show modest correlations between measures of lung function and dyspnea ratings, previous investigators 27, 30 -32 have not shown significant differences in MRC dyspnea scores with different stages of COPD. Our results are the first to demonstrate that patient-reported dyspnea ratings on three different instruments are significantly related to the stage of disease severity based on percent predicted FEV 1 in patients with COPD.…”
Section: Discussionmentioning
confidence: 94%
“…For the BDI (visits 1 and 2), the patient selected grades for each of the three components, which were summed to obtain a total score (0 to 12). 8,16 Lower scores represent more breathlessness. Using the TDI (visits 3 and 4), patients reported changes in breathlessness from baseline for each component by adjusting the length of a bar along a bidirectional visual analog scale.…”
Section: Sac Versions Of the Bdi And Tdimentioning
confidence: 99%
See 2 more Smart Citations
“…In this multicentre, blinded, double-dummy, three-period crossover study, 247 patients were randomized to once-daily QVA149 110/50 µg, placebo or tiotropium 18 µg. Superiority of QVA149 versus placebo (primary objective) and tiotropium (secondary objective) was assessed for improvement in dyspnoea via the Self Administered Computerized (SAC) version of the Baseline and Transition Dyspnoea Index (BDI/TDI) after 6 weeks 4 .…”
Section: Methodsmentioning
confidence: 99%